Use of Economic Compensation to Increase Demand for Voluntary Medical Male Circumcision in Kenya: Qualitative Interviews With Male Participants in a Randomized Controlled Trial and Their Partners. (1st October 2016) - Evens, Emily; Lanham, Michele; Murray, Kate; Rao, Samwel; Agot, Kawango; Omanga, Eunice; Thirumurthy, Harsha
Abstract : Background: Interventions to increase demand for medical male circumcision are urgently needed in eastern and southern Africa. Following promising evidence that providing economic compensation can increase male circumcision uptake in Kenya, there is a need to understand the role of this intervention in individuals' decision-making regarding circumcision and explore perceptions of the intervention and concerns such as coercion. Methods: As part of a randomized controlled trial in Kenya that found compensation in the form of food vouchers worth US $8.75–US $15.00 to be effective in increasing male circumcision uptake, we conducted qualitative in-depth interviews with 45 circumcised and uncircumcised male participants and 19 female partners to explore how compensation provision influenced the decision to get circumcised. Interview transcripts were coded and an inductive thematic analysis was conducted to identify patterns in decision-making. Results: Interviews revealed that compensation promoted circumcision uptake by addressing a major barrier to male circumcision uptake: lost wages during and after the circumcision procedure. Participants who did not get circumcised perceived the compensation amounts to be insufficient for offsetting their costs associated with getting circumcised or reported having nonfinancial barriers that were not addressed by the intervention, such as fear of pain. Participants also reported that they did not feel compelled to get circumcised for financial gain. Female partners of circumcised participants felt that the intervention helped to motivate their partners to get circumcised. Conclusions: The results suggest that the provision of economic compensation is an acceptable intervention that can address an important barrier to male circumcision uptake. Providing compensation to circumcision clients in the form of food vouchers warrants further consideration in voluntary medical male circumcision demand creation efforts.